High level cognitive process of high school students in solving mathematics problems based on learning style - Irma Zahrotul Jamilah; Raden Sulaiman; Pradnyo Wijayanti (Math Didactic: Jurnal Pendidikan Matematika, 2021)
This research aim is to describe the high-level cognitive processes of high school students in solving mathematics problem based on visual, auditory, and kinesthetic learning style. The subjects of this research were three students which chosen from thirty-two students of class XII-1 SMAN 15 Surabaya based on visual, auditory, kinesthetic and who have the same mathematic skill. Instrument in this research include researcher, mathematic ability test, learning style questionnaire, mathematic problem-solving test, and interview guidelines. The analysis process in student’s sheet is based on high level cognitive process Anderson and Krathwohl which cover analyzing, evaluating, creating and Polya problem solving steps. The results showed that visual, auditory, and kinesthetic students went through different high level cognitive processes. Kinesthetic student can through high level cognitive processes to the cognitive process planning. Visual and auditory students can through high level cognitive processes to the cognitive process critiquing. Students need to be trained to solve mathematic problems in a variety way.